2022
DOI: 10.1021/acs.analchem.2c03515
|View full text |Cite
|
Sign up to set email alerts
|

Living Cell-Target Responsive Accessibility Profiling Reveals Silibinin Targeting ACSL4 for Combating Ferroptosis

Abstract: We report a living cell-target responsive accessibility profiling (LC-TRAP) approach to identify the targetome of silibinin (SIL), a well-established hepatoprotective natural product (NP), in HepG2 cells. Proteins showing accessibility changes, probed by covalent lysine labeling reagents and leveraged by multiplexed quantitative proteomics, following the administration of SIL to the living cells were assigned as potential targets. Among the assigned targetome, ACSL4, an enzyme essential for ferroptosis inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…128 Specifically, biochanin A not only alleviated intracellular iron overload by upregulating the expression of SLC40A1 and down-regulating the expression of TFR but also reduced lipid peroxidation by regulating the NRF2/SLC7A11/GPX4 axis. These findings suggest that most isoflavones can simultaneously target 132 Further studies confirmed that silibinin could suppress the enzymatic activity of ACSL4 by directly binding to it, which inhibited ferroptosis in hepatocytes and thus exerted hepatoprotective effects. Dihydroquercetin, a plant flavanonol isolated from yew, protected against SiO 2 -induced lung fibrosis in C57BL/6 mice.…”
Section: Flavanonesmentioning
confidence: 72%
See 1 more Smart Citation
“…128 Specifically, biochanin A not only alleviated intracellular iron overload by upregulating the expression of SLC40A1 and down-regulating the expression of TFR but also reduced lipid peroxidation by regulating the NRF2/SLC7A11/GPX4 axis. These findings suggest that most isoflavones can simultaneously target 132 Further studies confirmed that silibinin could suppress the enzymatic activity of ACSL4 by directly binding to it, which inhibited ferroptosis in hepatocytes and thus exerted hepatoprotective effects. Dihydroquercetin, a plant flavanonol isolated from yew, protected against SiO 2 -induced lung fibrosis in C57BL/6 mice.…”
Section: Flavanonesmentioning
confidence: 72%
“…In addition, other types of flavonoids, including flavanonols, flavanols, and biflavonoids, can also act as potent regulators of ferroptosis. Yan et al discovered that ACSL4 was the target of silibinin in HepG2 cells by developing a living cell-target responsive accessibility profiling . Further studies confirmed that silibinin could suppress the enzymatic activity of ACSL4 by directly binding to it, which inhibited ferroptosis in hepatocytes and thus exerted hepatoprotective effects.…”
Section: Natural Flavonoids Targeting Ferroptosismentioning
confidence: 99%
“…TEPP-46 binds and activate PKM2 (pyruvate kinase M2) by promoting the tetramerization of the protein (30). A recent work treated cells with TEPP-46 followed chemical labelling after cell lysis with isotope-coded formaldehyde (CD2O) to identify structural conformation changes induced in PMK2 (31). To further validate the use of RAPID-OPA to study conformational changes in protein structures directly in cells, HEK293T cells were treated with TEPP-46 for 20 min, followed by RAPID-OPA where proteins were labelled with OPA before cell lysis and analyzed with MS in PRM mode (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The integration of protein-denaturation principles with lysine-reactive qXL-MS provides a protein–ligand assay. Utilizing additional strategies such as Activity-Based Protein Profiling and Target-Responsive Accessibility Profiling could allow greater orthogonal access in evaluating ligand–target interactions. , The strategy presented has the potential to complement other protein-denaturation MS-based approaches in studying drug–target interactions on the cellular scale.…”
Section: Discussionmentioning
confidence: 99%